2004
DOI: 10.1002/sdr.289
|View full text |Cite
|
Sign up to set email alerts
|

Misperceptions of basic dynamics: the case of renewable resource management

Abstract: Previous laboratory experiments, using quite complex resource simulators, suggest that renewable resources are over-utilised because of a general tendency for people to systematically misperceive the dynamics of bioeconomic systems. Here, similar experiments with simplified simulators involving the management of reindeer rangelands are carried out. Sufficient information is given for the subjects to construct perfect mental models. Misperceptions persist for a simulator containing only the basic building block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 20 publications
(10 reference statements)
3
132
0
3
Order By: Relevance
“…For example, participants in simulated fisheries frequently expand their fleets beyond the maximum sustainable yield, forcing the system over the tipping threshold into the regime in which smaller fish stocks reduce recruitment, leading to still lower stocks and the collapse of the fishery. Overshooting the tipping point persists in laboratory experiments even when the common pool resource problem (the Tragedy of the Commons) is eliminated by assigning perfect property rights (Moxnes 1998(Moxnes , 2004.…”
Section: Foldsmentioning
confidence: 99%
“…For example, participants in simulated fisheries frequently expand their fleets beyond the maximum sustainable yield, forcing the system over the tipping threshold into the regime in which smaller fish stocks reduce recruitment, leading to still lower stocks and the collapse of the fishery. Overshooting the tipping point persists in laboratory experiments even when the common pool resource problem (the Tragedy of the Commons) is eliminated by assigning perfect property rights (Moxnes 1998(Moxnes , 2004.…”
Section: Foldsmentioning
confidence: 99%
“…To be better prepared for and resilient to uncertainty and disturbances in the future, they need to further develop knowledge about the food and farming system as a system, with its dominating feedback structures and complexities. Such knowledge and understanding is critical for continuous adaptation and for testing robust and integrated system-based solutions (Holling, 2001, Wiek et al, 2011, as feedback structures and complexity often cause well-intentioned solutions to have unanticipated consequences (e.g., Moxnes, 2004;Sterman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Moxnes (1998aMoxnes ( , 1998bMoxnes ( , 2000Moxnes ( , 2004 in experiments concerning renewable resources using simple dynamic systems has shown that humans have strong tendencies to over utilize and over invest resources. In experiments when subjects were asked to set reindeer quotas in a district where lichen has been severely depleted by preceding overgrazing, Moxnes (2004) shows that all subjects make an error of overexploitation. According to Moxnes (2004), the plausible explanation for this behavior is faulty "static correlation mental models" where humans fail to distinguish between stock (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments when subjects were asked to set reindeer quotas in a district where lichen has been severely depleted by preceding overgrazing, Moxnes (2004) shows that all subjects make an error of overexploitation. According to Moxnes (2004), the plausible explanation for this behavior is faulty "static correlation mental models" where humans fail to distinguish between stock (i.e. accumulation) and flows (time derivatives) that cause the stock to change.…”
Section: Introductionmentioning
confidence: 99%